Cyclic guanosine monophosphate modulates locomotor acceleration induced by nitric oxide but not serotonin in Clione limacina central pattern generator swim interneurons - Pirtle, Thomas; Satterlie, Richard (Zenodo, 2021)
Typically, the marine mollusk, Clione limacina , exhibits a slow, hovering locomotor gait to maintain its position in the water column. However, the animal exhibits behaviorally relevant locomotor swim acceleration during escape response and feeding behavior. Both nitric oxide and serotonin mediate this behavioral swim acceleration. In this study, we examine the role that the second messenger, cGMP, plays in mediating nitric oxide and serotonin induced swim acceleration. We observed that application of an analogue of cGMP or an activator of soluble guanylyl cyclase, increased fictive locomotor speed recorded from Pd-7 interneurons of the animal's locomotor central pattern generator. Moreover, inhibition of soluble guanylyl cyclase decreased fictive locomotor speed. These results suggest that basal levels of cGMP are important for slow swimming and that increased production of cGMP mediates swim acceleration in Clione . Because nitric oxide has its effect through cGMP signaling and because we show herein that cGMP produces cellular changes in Clione swim interneurons that are consistent to cellular changes produced by serotonin application, we hypothesize that both nitric oxide and serotonin function via a common signal transduction pathway that involves cGMP. Our results show that cGMP mediates nitric oxide-induced but not serotonin-induced swim acceleration in Clione . The following is a summary of the data set components. Supplement 1 Fig. 1 Effect of 8-Br-cGMP on Fictive Swim Frequency This Excel file summarizes the data showing how 8-Br-cGMP changes fictive swim frequency recorded from Pd-7 swim interneurons of the Clione swim central pattern generator. The first sheet summarizes all of the data used in this figure, including statistical results. Subsequent sheets show the individual data for these experiments. Supplement 2 Fig. 2 Effect of ODQ + NO on Fictive Swim Frequency This Excel file summarizes the data showing that ODQ, an inhibitor of soluble guanylyl cyclase, prevents nitric oxide from causing an ...